1998
DOI: 10.1046/j.1365-2648.1998.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Social support and locus of control as correlates of UK nurses’ health‐related behaviours

Abstract: Locus of control is more strongly associated with United Kingdom nurses' health-related behaviours than social support. Given the empirical links between nurses' health-related behaviours and their tendency to counsel clients about health issues, attempts to improve nurses' internal locus of control may ultimately improve their health promotion role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
0
24
0
2
Order By: Relevance
“…In general, studies based on larger samples found expected associations [9-12], whereas studies using smaller samples did not [13,14]. Furthermore, within the LOC dimensions, findings differed by form of health behaviour, with clearer associations for smoking [10,11,15,16] or less physical activity [11,17] than for alcohol consumption [9,11,13] or unhealthy nutrition [18]. Several explanations were proposed for this complex picture [11,13,19].…”
Section: Resultsmentioning
confidence: 99%
“…In general, studies based on larger samples found expected associations [9-12], whereas studies using smaller samples did not [13,14]. Furthermore, within the LOC dimensions, findings differed by form of health behaviour, with clearer associations for smoking [10,11,15,16] or less physical activity [11,17] than for alcohol consumption [9,11,13] or unhealthy nutrition [18]. Several explanations were proposed for this complex picture [11,13,19].…”
Section: Resultsmentioning
confidence: 99%
“…Social support also refers to the physical and emotional sources provided to people by interpersonal communication [18]. In other words, it is an exchange of resources between two persons or more, and these resources are perceived by the provider or the receiver to improve the receiver’s health [19, 20]. According to Toronton and colleagues (2006), social support consists of three key dimensions: an informational dimension (like advice or guidance), an emotional dimension (such as feeling loved, esteemed, and valued), and an instrumental dimension (like tangible assistance) [21].…”
Section: Introductionmentioning
confidence: 99%
“…Social support is an exchange of resources between at least two individuals; resources perceived by the provider or the recipient to be intended to promote the health of the recipient [2,3]. Although numerous definitions have been used to evaluate the concept of social support, it falls into two categories.…”
Section: Introductionmentioning
confidence: 99%